Uji Laju Korosi Material Besi Tulang Struktur Bangunan Dengan Media Air Hujan - Kadir, Ihsan (SAINFIS: Jurnal Sains Fisika, 2022)
Research has been conducted to analyze the corrosion rate experienced by iron concrete buildings dipped in rainwater media. Analysis of the corrosion rate of concrete iron buildings was carried out using the method of mass loss. Mass measurements of samples were carried out before and after immersion in rainwater media. To determine the effect of dyeing time on corrosion rate, dyeing time is varied from 7 days, 14 days, 21 days, and 28 days. Based on the analysis and discussion, it can be concluded that the corrosion rate of concrete bone iron with prolonged contact and 7 to 28 days rainwater is in the range of 1,21-1,81 mm/year for concrete iron 1 and 1,21-1,66 mm/year for concrete iron 2. This shows that the time of contact with rainwater affects the corrosion rate of both types of iron. Therefore, in the selection of building materials, in addition to considering SNI must also consider the storage and installation of iron so that iron can be protected from contact with rainwater. So, the quality of the building can be better condition.